PERÚ Y LA ESTRATEGIA ARMADA EN LOS AÑOS SESENTA: LA REACTUALIZACIÓN DE UN DEBATE - MANGIANTINI, MARTÍN (Universidad Nacional del Litoral, 2016)
At the beginning of the sixties, the Trotskyist Argentine organization Palabra Obrera (Working Word) decided to send three militants to Peru with the aim of construction and of political insertion in a context of important social convulsion, principally from the capture of land and the rural unionization in the region of the Cuzco. The implementation of armed actions by this group generated a process of discussion and debate that, recently, was brought to collation immediately after a series of new documentary inputs. It is the aim of this article to analyze this fact in the light of these brand new discussion tools.